The method of negation in the Arabic language in light of the Holy Quran - Bin Ahmad, Ali (Arab Journal for Sciences and Research Publishing, 2016)
Method of negation is the linguistic phenomenon common in Arabic language; therefore, many tools, and varied manifestations. Ancient grammarians differed in the interpretation of this phenomenon and develop its provisions; because they did not relate the linguistic reality interpreted in Arabic, but simply described the level of compositional construction. This search is a modest attempt to explore the phenomenon of negative structures. Through the dialectal dimension and semantic dimension; and all this in the light of Koranic readings and Arabic poetry. Also we want to emphasize the important relationship between the grammar lesson and dialectal lesson and Koranic readings in order to reach a sound directed toward me and away from the arbitrariness of some grammarians.